Enhanced ferroelectric and piezoelectric properties in doped lead-free (Bi0.5Na0.5)0.94Ba0.06TiO3 thin films - Wang, D.; Chan, N.; Choy, S.; Tian, Hu-Yong; Chan, L.; Li, S (American Institute of Physics, 2010)
Doping effects with respect to the electrical properties of morphotropic phase boundary Bi0.5Na0.50.94Ba0.06TiO3 thin films epitaxially grown on CaRuO3 electroded LaAlO30.3Sr2AlTaO60.35 (001) substrates were investigated. Substantial enhancement of ferroelectricity and piezoelectricity has been achieved in La+Ce codoped films with a remanent polarization Pr of 29.5 C/cm2 and a remanent piezoelectric coefficient d33f of 31 pm/V, whereas Mn doping seems more favorite to reduce the leakage current by two order of magnitude. Both doped films exhibited diodelike I-V characteristics, which are correlated with resistance switching effect.